A behavioural analysis of the newsvendor game: Anchoring and adjustment with and without demand information. (September 2017) - D'Urso, Diego; Di Mauro, Carmela; Chiacchio, Ferdinando; Compagno, Lucio
Highlights: Human decision making is focused as regard to the Newsvendor game. Controlled human experiments are performed. A model taking into account more than one kind of management style is coded. Individuals follow an Anchoring and Adjustment heuristic (An&Ad). An&Ad and demand chasing heuristics simultaneously affect individuals. Abstract: Production systems are the combined result of technologies, organization, and individual behaviour. The impact of the human factor on the efficacy and efficiency of production systems is difficult to predict, since it often escapes the predictions of orthodox models of rationality. Recent behavioural studies in Operations Management highlight that the Human's behaviour deviates from the optimal solution, even in simplified operating conditions such as those represented by the famous Newsvendor problem. Building on the results of controlled human experiments, this study proposes a decision-making model that accounts for the heuristics of anchoring and adjustment. Two experimental conditions, differing in the provision of demand information to decision makers, are used to generate data. The model estimated shows that anchoring and adjustment behaviour differs in the two conditions.